Religious Plurality and Pluralism in Indonesia: Western Influence on Liberal Muslim Intellectuals - Mahmuluddin, Mahmuluddin (Center of Islamic and Occidental Studies, 2024)
This research explores the critical distinction between religious pluralism and religious plurality within Islamic thought, addressing a common misconception among contemporary Muslim intellectuals influenced by Western ideologies. The study employs a qualitative methodology that includes a historical analysis of the emergence of religious pluralism during the European Reformation, an epistemological evaluation of hermeneutics in interpreting Islamic texts, and a critique of the adoption of Western pluralist frameworks by Indonesian Muslim intellectuals. The research showed that religious pluralism, understood as the acceptance of all religions as equally valid, is derived from a Western context and is at odds with Islamic teachings, which recognise religious plurality but maintain the exclusivity of Islam as the final revelation. The research highlights the Indonesian Ulema Council's rejection of religious pluralism while advocating tolerance. In addition to clarifying misconceptions about Islamic perspectives on religious diversity, the study highlighted the need to distinguish between acceptance of plurality and endorsement of pluralism, thereby contributing to more informed interfaith dialogue and understanding. Ultimately, the research improved the representation of Islamic thought in academic and public discussions and to encourage a more nuanced appreciation of its theological underpinnings regarding religious diversity.